PELATIHAN PENGGUNAAN APLIKASI VIRTUAL LEARNING DI TPA ZIYAADATUL HASANAH - Nazmia Kurniawati; Henry Candra; Yuli Kurnia Ningsih; Alfred Pakpahan; Tri Swasono Adi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
Since the outbreak of the Corona Virus Disease (Covid-19) case in March 2020, the government issued a policy to conduct distance learning. Conditions that require learning activities to be carried out online caused the children to to use applications to carry out learning activities. One of the obstacles in implementing distance learning activities is the lack of technology mastery by parents and children. This causes children to have difficulty in learning the material provided by the school. In this activity, training was conducted to use virtual learning applications as learning media with the target of active parents and students in TPA Ziyaadatul Hasanah, Duren Sawit. With this training, it is hoped that parents and students can use virtual learning applications. So that parents can guide their sons and daughters in conducting distance learning activity and students are not left behind due to internet connection problems. From the results of the questionnaire given to participants to measure understanding of the training, participants gained increased knowledge about virtual learning applications as proofed by the increase in scores obtained from the pre-test and post-test results. In the pre-test the average score obtained by the participants was 8.3 while in the post-test the average score was 9.45 out of a scale of 10. In terms of satisfaction, the average score given by the participants was in the range of 4.1 to 4.75 and belongs to the very good range. Based on the results of discussions with participants, participants expected that there would be further activities related to their problems to be provided by the community service team.ABSTRAKSejak merebaknya kasus Corona Virus Disease (Covid-19) pada bulan Maret 2020, pemerintah mengeluarkan kebijakan untuk melakukan pembelajaran secara jarak jauh (PJJ). Kondisi yang mengharuskan kegiatan pembelajaran dilakukan secara daring menyebabkan anak-anak harus menggunakan aplikasi untuk melakukan kegiatan pembelajaran. Salah satu kendala dalam pelaksanaan kegiatan PJJ adalah kurangnya penguasaan teknologi oleh orang tua dan anak. Hal tersebut menyebabkan anak-anak kesulitan dalam mempelajari materi yang diberikan. Pada kegiatan ini dilakukan pelatihan penggunaan aplikasi virtual learning sebagai media pembelajaran dengan sasaran orang tua dan siswa yang aktif di TPA Ziyaadatul Hasanah, Duren Sawit. Dengan adanya pelatihan ini diharapkan orang tua dan siswa dapat menggunakan aplikasi virtual learning. Sehingga orang tua dapat membimbing putra putrinya dalam PJJ dan siswa tidak tertinggal materi karena masalah koneksi internet. Dari hasil kuesioner yang diberikan kepada peserta untuk mengukur pemahaman terhadap pelatihan yang diberikan, peserta mendapatkan peningkatan pengetahuan mengenai aplikasi virtual learning yang dibuktikan dengan peningkatan nilai yang didapatkan dari hasil pre-test dan post-test. Pada pre-test nilai rata-rata yang didapatkan peserta adalah 8.3 sedangkan pada post-test rata-rata nilainya adalah 9.45 dari skala 10. Sementara dari sisi kepuasan, rata-rata skor yang diberikan oleh peserta berada pada rentang 4.1 hingga 4.75 dan termasuk ke dalam rentang sangat baik. Berdasarkan hasil diskusi dengan peserta, warga mengharapkan adanya kegiatan lanjutan dari pelatihan virtual learning yang dilakukan pada periode PkM ini.